2011
DOI: 10.1124/dmd.110.037382
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Toll-Interleukin 1 Receptor Domain-Containing Adaptor Protein in Toll-Like Receptor 2-Mediated Regulation of Gene Expression of Hepatic Cytokines and Drug-Metabolizing Enzymes

Abstract: LTA-mediated down-regulation of DME genes was attenuated in hepatocytes from TLR2(؊/؊) or TIRAP(؊/؊) mice and in small interfering RNA-treated hepatocytes. Thus, the effect of TLR2 on DME genes in hepatocytes was mediated by TIRAP, whereas TIRAP was not involved in mediating the effects of TLR2 on cytokine expression in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
0
33
1
Order By: Relevance
“…These cytokines act on hepatocytes to reduce the expression of DME/transporter genes (Renton, 2004;Aitken et al, 2006). We have also shown that activation of TLR2 by lipoteichoic acid (LTA) (Gram-positive bacterial component) downregulates the expression of select DME and transporter genes (Ghose et al, 2009(Ghose et al, , 2011.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…These cytokines act on hepatocytes to reduce the expression of DME/transporter genes (Renton, 2004;Aitken et al, 2006). We have also shown that activation of TLR2 by lipoteichoic acid (LTA) (Gram-positive bacterial component) downregulates the expression of select DME and transporter genes (Ghose et al, 2009(Ghose et al, , 2011.…”
Section: Introductionmentioning
confidence: 89%
“…The sequences of the primers and probes were obtained from the literature, as reported previously (Ghose et al, 2004(Ghose et al, , 2009(Ghose et al, , 2011. All oligonucleotides were purchased from Sigma Genosys (Houston, TX), and all real-time polymerase chain reaction (PCR) reagents were purchased from Applied Biosystems (Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms behind this P450 regulation have been investigated, and the nuclear factor k-light-chain-enhancer of activated B cells-dependent inflammatory response and associated relocalization and dimerization of nuclear receptors such as retinoid X receptor, liver X receptor, farnesoid X receptor, constitutive androstane receptor, pregnane X receptor (PXR), and peroxisome proliferator-activated receptor have been implicated (Jover et al, 2002, Yang et al, 2010Ghose et al, 2011). However, P450-specific transcriptional regulation has not been fully characterized, and the question of common pathways versus specific receptor-dependent intracellular signaling pathways is still to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Kupffer cells can release cytokines such as tumor necrosis factor a (TNF-a) and interleukin-6 (IL-6) which modulate suppression of CYP3A4 in hepatocytes in vitro (Hoebe et al, 2001;Sunman et al, 2004). Therapeutic proteins that are cytokines or cytokine modulators can suppress DME by acting directly on hepatocytes (Ghose et al, 2011) and/or Kupffer cells, as has been shown for interferon-a-2B (IFNa-2B) with theophylline and methadone clearance (Iafolla, 2002), whereas other therapeutic proteins, such as OKT3 antibody, cause systemic reaction by stimulating cytokine release from PBMCs (Abramowicz et al, 1989;Chatenoud et al, 1990;Herbelin et al, 1999;Wolf et al, 2012). The effects of therapeutic proteins that directly suppress drug metabolism can be examined in a traditional hepatocyte culture (Kraynov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%